2022
DOI: 10.3389/fpsyt.2022.941728
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of systemic immune-inflammation index, neutrophil/high-density lipoprotein ratio, lymphocyte/high-density lipoprotein ratio, and monocyte/high-density lipoprotein ratio as indicators of inflammation in patients with schizophrenia and bipolar disorder

Abstract: BackgroundThe systemic immune-inflammation index (SII), system inflammation response index (SIRI), neutrophil/high-density lipoprotein (HDL) ratio (NHR), lymphocyte/HDL ratio (LHR), monocyte/HDL ratio (MHR), and platelet/HDL ratio (PHR) have been recently investigated as new markers for inflammation. The purpose of this research is to use large-scale clinical data to discuss and compare the predictive ability of the SII, SIRI, NHR, LHR, MHR, and PHR in patients with schizophrenia (SCZ) and bipolar disorder (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 52 publications
2
38
2
1
Order By: Relevance
“…This means that NMOSD patients with high MLR should prolong first-line therapy or receive second-line therapy earlier to prevent recurrence. Wang et al (2022) found that MLR was associated with the prognosis of acute ischemic stroke and speculated that MLR might be related to the level of inflammation. However, our results did not find significant changes in MLR levels in patients with NMOSD, suggesting abnormalities in the function, but not the number, of monocytes and lymphocytes in active NMOSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that NMOSD patients with high MLR should prolong first-line therapy or receive second-line therapy earlier to prevent recurrence. Wang et al (2022) found that MLR was associated with the prognosis of acute ischemic stroke and speculated that MLR might be related to the level of inflammation. However, our results did not find significant changes in MLR levels in patients with NMOSD, suggesting abnormalities in the function, but not the number, of monocytes and lymphocytes in active NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…NLR, PLR and MLR were found to be associated with disease activity in polymyalgia rheumatica ( Jung et al, 2019 ). SII and SIRI were also significantly higher in patients with schizophrenia and bipolar disorder than in normal people ( Wei et al, 2022 ). During the COVID-19 epidemic, NLR, PLR, MLR, SII and SIRI all effectively predicted death ( Ghobadi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Sahpolat et al first found significant differences in the MHR between patients with schizophrenia and healthy populations in a small sample study [ 37 ]. In 2022, Yanyan Wei et al recruited 13,329 patients with schizophrenia, 6005 patients with bipolar disorder and 5810 healthy people for a study, and subsequently found that the MHR could be used as a distinguishing factor between healthy people and SCZ patients [ 38 ]. Although it is true that there are relatively few inflammatory markers of this class in research on psychiatric disorders—which is in the exploratory phase—there are studies demonstrating the relationship of this class of indicators to psychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lower serum HDL-C levels were associated with higher odds of having depression, and the immune/inflammatory response may contribute to lower serum HDL-C in depressive populations (Maes et al, 1997). Furthermore, the LHR was significantly associated with psychiatric diseases according to a previous study (Wei et al, 2022). Second, inflammatory and oxidative stress might be another reason contributing to the relationship between LHR and depression.…”
Section: Discussionmentioning
confidence: 81%